SISTEM INFORMASI PENGOLAHAN ASET DESA PADA KANTOR DESA MANDIANGIN TUO: Village, Village Asset Management, System, Fast, Efficien - Elzas; Puad, Lailyn; Irawan, Ridho (LP2M Universitas Nurdin Hamzah, 2023)
Village assets are village assets originating from the village's original assets, purchased orobtained at the expense of the Village Revenue and Expenditure Budget (APBDesa), Village Asset Management at the Mandiangin Tuo Village Office is carried out by recording it on paper and storing it in a special village file cabinet. This causes many errors to occur, and spend a lot of time searching for the data. In order for inventoryrecords and goods mutations to be more precise and accurate and easier to do in recording the existence of these goods,the Mandiangin Tuo Village Officer equires an application in the form of a website.